2020
DOI: 10.1186/s12889-020-8218-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends in self-rated health among the elderly population in Germany from 1995 to 2015 – the influence of temporal change in leisure time physical activity

Abstract: Background: Against the backdrop of rising statutory retirement age in Germany, we analyzed time trends in selfrated health (SRH) among the elderly population between 50 and 70 years of age and explored the mediating role of leisure time physical activity (LTPA) on the relationship between time period and self-rated health (SRH). Methods: We used longitudinal survey data (n = 23,161) from a national panel study (GSOEP) to analyze time trends in SRH and regular LTPA (at least once a week) by means of Generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…We found the MCS is associated with daily moving time ( r s = 0.538, p = 0.014) and distance ( r s = 0.556, p = 0.011). The results of this study are consistent with the previous literature [ 55 , 60 ]. However, the PCS does not show a correlation in the three aspects of mobility.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We found the MCS is associated with daily moving time ( r s = 0.538, p = 0.014) and distance ( r s = 0.556, p = 0.011). The results of this study are consistent with the previous literature [ 55 , 60 ]. However, the PCS does not show a correlation in the three aspects of mobility.…”
Section: Resultssupporting
confidence: 94%
“…It is reported that the frequency of going outdoors is directly linked to levels of physical activity among community-dwelling older people, and practicing moderate physical activity could amortize its negative effects on psychological health [ 55 ]. Additionally, the increase of regular leisure time physical activity accounted for improved SRH [ 56 , 57 , 58 , 59 , 60 ]. The more restricted activities in daily life, the worse mental health, and the lower self-rated health score [ 61 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results showed that participants with higher total PA were more likely to rate their health as good, which is in accordance with prior research [35,36]. In line with our results, a study by Riebe et al [37] found an association between higher PA and a lower risk of obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Our results regarding total PA are in line with previous research. Total PA is linked to better self-rated health [43,44], overweight and obesity [45], and physical functioning [46,47]. Our study showed a statically significant higher objectively measured PA in women compared to men.…”
Section: Discussionmentioning
confidence: 48%